1999
DOI: 10.1086/303269
|View full text |Cite
|
Sign up to set email alerts
|

Variability and Parasitoid Foraging Efficiency: A Case Study of Pea Aphids and Aphidius ervi

Abstract: When a parasitoid is searching for hosts, not all hosts are equally likely to be attacked. This variability in attack probability may affect the parasitoid functional response. Using a collection of experiments, we quantified the functional response of Aphidius ervi (Hymenoptera: Braconidae), an insect parasitoid of the pea aphid Acyrthosiphon pisum (Homoptera: Aphididae). We measured variability in the number of hosts attacked by a foraging parasitoid both among plants and within plants. At the first scale, A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
88
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(95 citation statements)
references
References 49 publications
6
88
0
1
Order By: Relevance
“…Since only one wasp can complete development in a single aphid, self-superparasitism (more than one egg laid by the same mother) by solitary endoparasitoids like A. ervi has generally been considered maladaptive, yet wide-ranging conditions have been proposed under which this strategy may be adaptive [51]. If the net fitness of offspring is higher under conditions of superparasitism compared to single-parasitism then selection may favor the sacrifice of an additional egg for a parasitoid such as A. ervi , which is limited by their time to find hosts rather than the number of eggs they have [25,53]. Aphidius ervi has a large number (96 to 567) of small, yolk-free eggs during adulthood (for example, [54,55]).…”
Section: Discussionmentioning
confidence: 99%
“…Since only one wasp can complete development in a single aphid, self-superparasitism (more than one egg laid by the same mother) by solitary endoparasitoids like A. ervi has generally been considered maladaptive, yet wide-ranging conditions have been proposed under which this strategy may be adaptive [51]. If the net fitness of offspring is higher under conditions of superparasitism compared to single-parasitism then selection may favor the sacrifice of an additional egg for a parasitoid such as A. ervi , which is limited by their time to find hosts rather than the number of eggs they have [25,53]. Aphidius ervi has a large number (96 to 567) of small, yolk-free eggs during adulthood (for example, [54,55]).…”
Section: Discussionmentioning
confidence: 99%
“…One of the few studies that examined the temporal pattern in the heterogeneity of parasitism showed that there was much variation between years (Jones et al 1993). Ives et al (1999) present an alternative, suggesting that the presence of large amounts of variability reduce the importance of aggregating and functional responses that occur over small spatial scales. We would need parasitism data for several years or a functional response experiment over a wide variety of densities to fully predict the long term impact of densitydependent parasitism on the stability of the system.…”
Section: Implications For Dynamicsmentioning
confidence: 99%
“…The correlation between spatial patchiness and functional response described in this model application can also be found in terrestrial food-webs. Parasitoid insects of the pea aphid, for example, turn from a type I response to type II when aphid density and, thus, spatial crowding of host increases (Ives et al 1999). An analog shift from type I to type II functional response also appears for fox squirrels when animals gather in a larger, more patchy habitat (Morgan et al 1997).…”
Section: Resultsmentioning
confidence: 99%